Demonstrating CO2 capture in the UK cement, chemicals, iron and steel and oil refining sectors by 2025 : A Techno-economic StudyFinal report for DECC and BIS.: A Techno-economic StudyFinal report for DECC and BIS. (2014) - Unknown
No abstract available